CECHY REŻIMU ODPŁYWU RZEK KOTLINY KŁODZKIEJ - PERZ, ADAM (Badania Fizjograficzne Seria A - Geografia Fizyczna, 2019)
This paper seeks to identify the features of the flow regime of the rivers in Kłodzka Valley in terms of the runoff, the structure and the spatiotemporal variabilities. The analysis was carried out on the basis of data provided by the Institute of Meteorology and Water Management from the period of 1971–2015 and obtained from 8 gauging stations located in 5 rivers. The research embraced the Nysa Kłodzka river and its main tributaries to the gauging station in Kłodzko. The runoff conditions in the analysed sub-basins are different. As a result, the rivers in Kłodzka Valley have different regime features. Due to the regularities in their flow variability, they can be classified into 2 types of hydrological regime: nival and nival-pluvial. There are significant differences in the total runoff, from 375 mm in Kłodzko to above 700 mm in the Wilczka river. The differences also occur in terms of the groundwater runoff and its contribution to the total runoff which ranges between 31% and 53%. All of the analysed basins have contributions to groundwater runoff below the mean value for the entire country (55%). In terms of viabilities of discharges, in general there are differences between the upper Nysa Kłodzka and its eastern tributaries and the western part of the basin.